Treatment of Human Urinary Kallidinogenase Combined with Maixuekang Capsule Promotes Good Functional Outcome in Ischemic Stroke - Song, Juexian; Lyu, Yi; Wang, Miaomiao; Zhang, Jing; Gao, Li; Tong, Xiaolin (Frontiers in Physiology, 2018)
Aims:To evaluate the clinical efficacy of Human Urinary Kallidinogenase (HUK) and Maixuekang capsule in the treatment of acute ischemic stroke (AIS) patients . Methods: In this study, from January 2016 to July 2016 ,60 patients with acute ischemic stroke were enrolled and 56 patients with complete information of whom 21 patients received HUK+ basic treatment(HUK group),16 patients received HUK+ Maixuekang capsule + basic treatment(HUK+ Maixuekang group),19 patients received basic treatment(control group) . 0.15 PNA unit of HUK injection plus 100 ml saline in intravenous infusion was performed in the HUK group and HUK+ Maixuekang group, with once a day for 14 consecutive days . 0.75g Maixuekang capsules were taken in HUK+ Maixuekang group , with three times a day for 14 consecutive days. The National Institutes of Health Stroke Scale(NIHSS) scores in three groups were analyzed 7 days after treatment. The modified Rankin Scale (mRS) scores in three groups were analyzed 12 months after the treatment. Results: No difference was found in the NIHSS scores, age, gender, and comorbidities between three groups before treatment (p > 0.05). 7-days after treatment, the NIHSS scores in the HUK group and HUK+ Maixuekang group were significantly decreased than before( p HUK=0.001, p HUK+ Maixuekang<0.001),and lower than that in the control group(p HUK=0.032;pHUK+Maixuekang<0.001).12-month after treatment, good recovery functional outcome rate (12-month mRS score ≤2) in the HUK group and HUK+ Maixuekang group wasere significantly higher than that in the control group(p HUK=0.049, p HUK+ Maixuekang=0.032). Conclusion: The treatment of HUK or HUK combined with Maixuekang capsule can effectively improve the neurological function and promote long-term recovery for AIS patients.